A retrospective review of patients admitted to the Paediatric ICU at Red Cross War Memorial Children's Hospital during 2010 with the clinical diagnosis of measles or measles-related complications - Coetzee, Saskia (Department of Paediatrics and Child Health, 2014)
Includes abstract. Includes bibliographical references.